Erythrocyte and reticulocyte indices in the assessment of erythropoiesis activity and iron availability - Urrechaga, E.; Borque, L.; Escanero, J. F. (International journal of laboratory hematology, 2013)
Summary Introduction Consequence of the imbalance between the erythroid marrow iron requirements and the actual supply is a reduction in red cell hemoglobin content, which causes hypochromic mature red cells and reticulocytes. Sysmex XE 5000 analyzer (Sysmex Corporation, Kobe, Japan) reports reticulocyte hemoglobin equivalent (Ret‐He) and the percentages of erythrocyte subsets, including the hypochromic fraction (%Hypo‐He). We study the value of these parameters of hemoglobinization in the evaluation of erythropoiesis and iron availability. Methods Ninety healthy subjects, 85 patients with chronic kidney disease (CKD) and 65 patients on dialysis (HD) receiving therapy and 91 patients with iron deficiency (IDA) were analyzed. Pearson's correlation, t‐test for independent, and receiver operating characteristic (ROC) curve analysis were utilized. Results The results in the IDA group reflected the state of iron depletion (low ferritin), low iron availability (low MCH and high percentage of hypochromic red cells (%Hypo‐He)), and iron‐restricted erythropoiesis (low Ret‐He). In the HD and CKD, the reticulocyte percentage showed the increased erythropoiesis, maintained due to treatment (Ret‐He over 30 pg) and good iron availability, MCH within reference range and %Hypo‐He slightly increased. The results of ROC curves analysis for the diagnosis of iron deficiency (gold standard sTfR > 21 nm) were as follows: Ret‐He area under curve (AUC) 0.935 cutoff 29.8 pg, sensitivity 90.7%, specificity 83.1%. % Hypo‐He AUC 0.925 cutoff 3.5%, sensitivity 87.3%, specificity 88.0%. Conclusions Percentage of hypochromic red cells and Ret‐He provide information about individual cell characteristics, so the hypochromic cells are detected and quantitated improving the evaluation of erythropoiesis and iron status.